A Study of the Properties of Bagasse Ash for the Possibility in Making Light Weight Block - To-on, Piyanat; Witchayaphong, Phattarasuda; Pansuwan, Jarungrat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
This research aimed to investigate the properties of bagasse ash in producing light-weight concrete block. In this work, the bagasse ash from the sugar industries was used as the raw material in the production. It was found that bagasse ash is the pozzolan because it is mixed with many silica and alumina which strengthen the concrete. The researchers designed 13 formula for the mixing ratio among dried bagasse, bagasse ash, and Portland cement. The mechanical properties were then tested. As the experimental results, the compression strength had the significant relationship with three compounds at the level of P < 0.05. From the analysis of each formula, a mixture of 2 percent dried bagasse, 65 percent bagasse ash, and 33 percent Portland cement gave the optimal compression strength at 1.4 MPa while the general light concrete block had compression strength of 0.6 MPa with around 30 percent different. However, the formula can be further developed in the future.